IABSE Conference, Rotterdam 2013: Assessment, Upgrading and Refurbishment of Infrastructures 2013
DOI: 10.2749/222137813806501533
|View full text |Cite
|
Sign up to set email alerts
|

Seismic Assessment of existing bridges in Croatia

Abstract: <p>Research on development of seismic assessment procedure for existing bridges will be presented in this paper. Both the linear response spectrum analysis and the nonlinear static pushover method are used and results were evaluated following the demands defined by current European seismic design codes. At first, this procedure is validated by its application to major Adriatic arch bridges with spans ranging from 200 m to almost 400 m as a part of an extensive project to develop their appropriate mainten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2
2

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 3 publications
0
8
0
Order By: Relevance
“…the locations that must be inspected and tested. Recommendations for the collection of data on arch bridges are developed based on the analogy with EN 1998-3 [1] for buildings, guidelines provided for bridges [7], and research on Croatian arch bridges [8][9][10][11]. Required knowledge levels, adequate data collection methods such as in-situ inspections (location and extension) for arch bridges, and confidence factors CF for determining properties of existing materials to be used in the analysis, are presented in Table 1.…”
Section: Bridge Inspection and Project Oversightmentioning
confidence: 99%
See 4 more Smart Citations
“…the locations that must be inspected and tested. Recommendations for the collection of data on arch bridges are developed based on the analogy with EN 1998-3 [1] for buildings, guidelines provided for bridges [7], and research on Croatian arch bridges [8][9][10][11]. Required knowledge levels, adequate data collection methods such as in-situ inspections (location and extension) for arch bridges, and confidence factors CF for determining properties of existing materials to be used in the analysis, are presented in Table 1.…”
Section: Bridge Inspection and Project Oversightmentioning
confidence: 99%
“…They provide answers about the expected bridge performance under a seismic event with acceptable accuracy, and indicate which are the most critical bridge details and elements. Based on the research conducted on Croatian arch bridges [8][9][10][11], it may be concluded that arches are not the most critical elements because they are characterized by great robustness as a result of their importance in crossing the obstacle. If bridge performance is deemed inadequate, appropriate counter-measures may be recommended based on these two assessment levels.…”
Section: Seismic Assessment Procedures For Reinforced Concrete Arch Brmentioning
confidence: 99%
See 3 more Smart Citations